Isomerização do N-hexano sobre catalisadores Pt-Ni suportados na zeólita H-BEA nanocristalina - Lima, Patrícia Moreira (2008)
This work had as a goal to investigate the main factors that explain the highest activity of zeolite Beta in relation to the other zeolitic structures, using the n-hexane isomerization as a criterion. With this goal, in this work monometallic catalysts of Pt and Ni, and bimetallic catalysts Pt-Ni were prepared using the commercial zeolite Beta with Si/Al global ratio equal to 9,0. For comparison, catalysts Pt-Ni supported on zeolite H-USY with Si/Al framework ratio equal to 11,0 were prepared. The method utilized to disperse the metals in the zeolite was the competitive ion exchange, using as precursors the amin complexes: [Pt(NH3)4]Cl2 and [Ni(NH3)6]Cl2. The catalysts were prepared with different molar contents of metal: 80, 130, 180 and 230 μmol metal/ gcat. After the ion exchange, the materials were calcined at 500 ºC under air flow and reduced by the method designated as 'rapid activation', in which a high rate heating and a high hydrogen flow are applied. The zeolites were characterized by XRD, 29Si MAS-NMR, 27Al MAS-NMR, HRSEM, HRTEM, ZLC and IR with adsorption of pyridine. The samples containing the metals were characterized by TPR, HRTEM and Hydrogen Chemisorption, and evaluated in n-hexane isomerization at 230 ºC. The zeolite Beta used (Si/Alglobal = 9,0) consists of nanosized crystallites (20-30 nm) aggregates, determined by HRTEM analysis. This result is too close to the average diameter of the crystallites obtained by XRD that was 14 nm. The influence of zeolite crystallites size in the desorption rates of n-paraffins was observed by ZLC method. The desorption curves obtained from zeolite Beta were well faster when compared to the ones obtained from zeolite USY (800 nm). The acidity analysis by IR with adsorption of pyridine showed that zeolite H-BEA presents lower quantity of Brønsted acid sites than zeolite H-USY, however these sites are stronger. Pt-Ni/HBEA catalysts showed much higher activity than Pt-Ni/HUSY ones. This behavior can be related to the much smaller crystallites of zeolite Beta, which increases the diffusion of molecules. Besides this, the very small crystallites of zeolite Beta increase the reduction of the metallic cations and the metals dispersion in the Pt-Ni/HBEA catalysts, what was observed by the TPR and Hydrogen Chemisorption techniques, respectively. Among the bimetallic samples with different Pt and Ni proportions, the higher activity was observed with the catalyst containing 60 % of Pt and 40 % of Ni. This result is very interesting due the costs reduction in relation to the platinum monometallic catalyst.